Review of Hungarian Journal of English and American Studies, Fall, 2017, Volume 23 Number 2 - Szélpál, Lívia (AMERICANA E-journal of American Studies in Hungary, 2018)
Hungarian Journal of English and American Studies, Fall, 2017, Volume 23 Number 2 Lenke Németh, ed. Institute of English and American Studies, University of Debrecen, Hungary, 2017. 213 pages ISSN: 1218-7364